2020
DOI: 10.3390/ani10122352
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Gut Bacterial Community Structure between Male and Female Stag Beetles Odontolabis fallaciosa (Coleoptera, Lucanidae)

Abstract: Odontolabis fallaciosa (Coleoptera: Lucanidae) is a giant and popular stag beetle with striking sexual dimorphism and male trimorphism. However, little is known about their intestinal microbiota, which might play an indispensable role in shaping the health of their hosts. The aim of this study was to investigate the intestinal bacterial community structure between the two sexes and among three male morphs of O. fallaciosa from China using high-throughput sequencing (Illumina MiSeq). The gut bacterial community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
9
3
Order By: Relevance
“…Contrary to the previous results with high gut bacterial diversity were found in female insects (Han et al, 2017;Mason et al, 2019;Wan et al, 2020;Xu et al, 2016), however, we found male spiders had significantly higher gut bacterial richness than female. Environmental factors have been proved to be an important role in gut microbiota assembly in arthropods (Chandler, Lang, Bhatnagar, Eisen, & Kopp, 2011;Wong, Chaston, & Douglas, 2013), for insects can obtain microbiota from their surrounding environments (Douglas, 2011).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the previous results with high gut bacterial diversity were found in female insects (Han et al, 2017;Mason et al, 2019;Wan et al, 2020;Xu et al, 2016), however, we found male spiders had significantly higher gut bacterial richness than female. Environmental factors have been proved to be an important role in gut microbiota assembly in arthropods (Chandler, Lang, Bhatnagar, Eisen, & Kopp, 2011;Wong, Chaston, & Douglas, 2013), for insects can obtain microbiota from their surrounding environments (Douglas, 2011).…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, Foster (1995) and Zouache et al (2011) considered that male mosquitoes disperse less than female which could be a factor constraining bacterial diversity, Ng, Stat, Bunce, & Simmons (2018) proved that reduced exposure to diverse environmental microbiota could decrease in gut bacterial diversity of insect. Minard et al (2013) found the different nutritional requirements between two sexes of mosquitos affect bacterial microbiota composition (e.g., higher relative abundance of Firmicutes and Firmicutes/Bacteroides (F/B) ratio, which contributed to nutritional efficiency (Wan et al, (2020). As a result, bacteria from generaBacillus and Staphylococcus were detected in male mosquitos, whereas Cryseobacterium , Pseudomonas andSerratia were present exclusively in female mosquitos (Rani, Sharma, Rajagopal, Adak & Bhatnagar, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minard et al (2013) also found that the different nutritional requirements between two sexes of mosquitos affected bacterial microbiota composition. Moreover, Wan et al (2020) showed that higher gut bacterial diversity in females might contribute to the vertical transmission. Although dramatically different activity habits between the two sexes were shown in spider variable species, the effect of sex on gut microbiota of spiders was almost ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Minard et al (2013) also found that the different nutritional requirements between two sexes of mosquitos affected bacterial microbiota composition. Moreover, Wan et al (2020) showed that…”
mentioning
confidence: 99%